Tumour necrosis factor receptor‐1 is dispensable for the migration of marginal metallophilic macrophages into the B‐cell zone of the mouse spleen. (6th August 2018) - Milićević, Đorđe N.; Despotović, Sanja Z.; Westermann, Jürgen; Milićević, Novica M.
Abstract: The spleen is the only blood filter in the organism which removes foreign antigens and effete cells from circulation. The significant role in capturing, transporting and presentation of antigens to immune cells is executed by a special subset of splenic macrophages called marginal metallophilic macrophages. Upon stimulation with lipopolysaccharide, these cells promptly migrate from their preferential location at the inner aspect of the splenic marginal sinus into the B‐cell lymphoid follicles. This migration is executed via CXC chemokine ligand 13 in a lymphotoxin‐dependent fashion. However, the role of tumour necrosis factor‐α/tumour necrosis factor receptor‐1 signalling axis has not been studied, despite its critical role in the formation of B‐cell lymphoid follicles, follicular dendritic cell networks and germinal centres. Here, we show that signalling via tumour necrosis factor receptor‐1 is not required for the migration of marginal metallophilic macrophages into the B‐cell zone and that the presence of organized B‐cell lymphoid follicles is not a prerequisite for their dislocation.